EVALUASI DAMPAK PENYULUHAN PERTANIAN METODE DEMONSTRASI CARA PEMBUATAN PUPUK BOKASHI DI DESA MOJOSARI KECAMATAN KEPANJEN - Babaro, Petronius Charbilo Baputra; Suwasono, Son; Nurhananto, Dwi Asnawi (Universitas Tribhuwana Tunggadewi, 2019)
The aim of agricultural extension is to create changes in knowledge, attitudes and skills and the process of adopting innovations that have been provided by extension agents to improve the standard of living, welfare and productivity of farmers. This study aims to analyze the implementation of agricultural extension demonstration of how to make the location of fertilizer fertilizer has an impact on improving the attitudes, knowledge and skills of farmers and the spread of innovation adoption. Determination of the sample using purposive sampling technique. The sample selection was done deliberately as many as 35 farmers. This research is a qualitatif descriptive study using a Likert scale. The results of this study are counseling demonstration methods how to manufacture bokashi fertilizer has an impact on increasing knowledge by 90.85%, attitudes of 86.58% and farmer skills by 89.14% with very high categories. Demonstration method of how to make bokashi fertilizer affects the spread of adoption of innovation with a very response category of 90.85%. Tujuan penyuluhan pertanian adalah menciptakan perubahan pengetahuan, sikap dan keterampilan dan proses penerapan adopsi inovasi yang telah diberikan oleh penyuluh agar meningkatkan taraf hidup, kesejahteraan hidup dan produktivitas hasil petani. Penelitian ini bertujuan untuk menganalisis pelaksanaan penyuluhan pertanian demonstrasi cara pembuatan pupuk bokasi berdampak pada peningkatan sikap, pengetahuan dan keterampilan petani dan penyebaran adopsi inovasi. Penentuan sampel menggunakan teknik purposive sampling. Pemilihan sampel dilakukan secara sengaja sejumlah 35 orang petani. Penelitian ini merupakan penelitian Deskriptif Kualitatif dengan menggunakan skala likert. Hasil dari penelitian ini adalah penyuluhan metode demostrasi cara pembuatan pupuk bokashi berdampak terhadap peningkatan pengetahuan sebesar 90,85%, sikap sebesar 86,58% dan keterampilan petani sebesar 89,14% dengan kategori sangat tinggi. Metode demostrasi cara pembuatan pupuk bokashi berdampak terhadap penyebaran adopsi inovasi dengan kategori sangat respon sebesar 90,85%.